Interleukin-17A signaling promotes CD8+ T cell cytotoxicity against West Nile virus infection through enhancing PI3K-mTOR-mediated metabolism. - Farzana Nazneen; Biswas Neupane; Yao Chen; Shazeed-Ul Karim; Zongbing You; Weiguo Cui; Fengwei Bai (PLoS Pathogens, 2025)
West Nile Virus (WNV), a mosquito-borne neurotropic flavivirus, is a major cause of viral encephalitis in the United States, posing a continuous threat to public health. Unfortunately, no vaccine or specific therapeutic intervention is available against WNV infection. Previous studies, including ours, demonstrated that interleukin-17A (IL-17A) signaling promotes the cytotoxicity of CD8+ T cells to facilitate WNV and parasite clearance; however, the molecular mechanism is not understood. IL-17 receptor C (IL-17RC) is an obligatory co-receptor with IL-17 receptor A (IL-17RA) for signaling induced by IL-17A, IL-17A/F, and IL-17F. In this study, we found that IL-17RC deficient (Il17rc-/-) mice were more susceptible to WNV infection with a higher viral load in the brain than wild-type (WT) control mice. The number of infiltrating WNV-specific CD8+ T cells and the expression levels of cytotoxicity mediators, such as perforin, in the T cells in the brain of Il17rc-/- mice were reduced. In addition, WNV-specific CD8+ T cells from IL-17RA deficient (Il17ra-/-) mice and CD8+ cell-specific Il17ra conditional knockout (cre-KO) mice expressed lower levels of perforin than their counterpart controls. Moreover, supplementing mouse recombinant IL-17A ex vivo increased the perforin production in WNV-specific CD8+ T cells from the WT mice but not Il17rc-/- or cre-KO mice. Interestingly, we found that IL-17A signaling activated the phosphatidylinositol-3-kinase/mammalian target of rapamycin (PI3K-mTOR) signaling pathway in CD8+ T cells, leading to increased metabolism of CD8+ T cells to cope with the higher energy demand for WNV clearance in the brain. In summary, our findings reveal a novel IL-17A-PI3K-mTOR signaling axis in promoting the effector functions of CD8+ T cells, suggesting potential broader implications in stimulating immune responses to combat WNV and other intracellular infections.